2023
DOI: 10.3390/ijms24054360
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances and Progress on Melanin: From Source to Application

Abstract: Melanin is a biological pigment formed by indoles and phenolic compounds. It is widely found in living organisms and has a variety of unique properties. Due to its diverse characteristics and good biocompatibility, melanin has become the focus in the fields of biomedicine, agriculture, the food industry, etc. However, due to the wide range of melanin sources, complex polymerization properties, and low solubility of specific solvents, the specific macromolecular structure and polymerization mechanism of melanin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(20 citation statements)
references
References 196 publications
0
20
0
Order By: Relevance
“…Similar results were reported on the HEP2 carcinoma cell line by Arun, et al [ 120 ], who reported that inhibition of cell viability was concentration-dependent and that 60 µg of melanin inhibited cell viability by 53%. Without harming or adversely affecting other healthy cells or bodily tissues, melanin offers anti-tumor properties that include apoptosis promotion and angiogenesis inhibition [ 126 ]. Melanin has good photothermal conversion efficiency and can absorb light from the ultraviolet to the near-infrared range.…”
Section: Resultsmentioning
confidence: 99%
“…Similar results were reported on the HEP2 carcinoma cell line by Arun, et al [ 120 ], who reported that inhibition of cell viability was concentration-dependent and that 60 µg of melanin inhibited cell viability by 53%. Without harming or adversely affecting other healthy cells or bodily tissues, melanin offers anti-tumor properties that include apoptosis promotion and angiogenesis inhibition [ 126 ]. Melanin has good photothermal conversion efficiency and can absorb light from the ultraviolet to the near-infrared range.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, it was thought that plant melanins belong to allomelanin which is devoid of nitrogen (Glagoleva et al ., 2020 ), despite a recent report that all three types (allomelanin, eumelanin and pheomelanin) are present in a medicinal plant Echinacea purpurea (Kurkiewicz et al., 2022 ) and nitrogen‐containing melanins may also be present in barley (Shoeva et al ., 2020 ). Our proposed pathway of melanin formation in barley seem to support the presence of multiple types of melanin as well, which may worth further attention because different types of melanin have been shown to retain varied biochemical properties (Guo et al ., 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among all flavonoids, neorauflavane (18) isolated from Camylotropishirtella is considered to be the most effective inhibitor (the IC50 of monophenolase and disphenolase activity is less than 0.5μm). The inhibitory activity is as high as 400 times that of kojic acid, and only reduces the content of melanin in B16 melanocytes without affecting the cell itself, which indicates that the reduction of geranyl side chain can improve tyrosinase inhibitory activity from the point of view of structure [11].…”
Section: Tyrosinase Inhibitorsmentioning
confidence: 93%